2010
DOI: 10.1111/j.1567-1364.2010.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial diseases and the role of the yeast models

Abstract: Nowadays, mitochondrial diseases are recognized and studied with much attention and they cannot be considered anymore as 'rare diseases'. Yeast has been an instrumental organism to understand the genetic and molecular aspects of the many roles of mitochondria within the cells. Thanks to the general conservation of mitochondrial genes and pathways between human and yeast, it can also be used to model some diseases. In this review, we focus on the most recent topics, exemplifying those for which yeast models hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 171 publications
(201 reference statements)
2
28
0
Order By: Relevance
“…Six different mutations in human mitochondrial tRNA Yeast was reported as a platform to understand the cellular role of human pathogenetic mitochondrial tRNAs, because mitochondrial tRNA sequence and function between yeast and humans are general conservative (55). For example, the A14G substitution of yeast mitochondrial tRNA Leu (UUR) caused equivalent aminoacylation defects and structure alterations to the A3243G human pathogenetic tRNA mutation (56).…”
Section: A Genetic Screen To Identify Functional Elements In Thrrs-mentioning
confidence: 99%
“…Six different mutations in human mitochondrial tRNA Yeast was reported as a platform to understand the cellular role of human pathogenetic mitochondrial tRNAs, because mitochondrial tRNA sequence and function between yeast and humans are general conservative (55). For example, the A14G substitution of yeast mitochondrial tRNA Leu (UUR) caused equivalent aminoacylation defects and structure alterations to the A3243G human pathogenetic tRNA mutation (56).…”
Section: A Genetic Screen To Identify Functional Elements In Thrrs-mentioning
confidence: 99%
“…The biolistic procedure was initially described by Johnston et al ( 1988 ) and Fox et al ( 1988 ) but has now been developed into a routine procedure . Since then, it has permitted to construct specifi c mitochondrialencoded mutations or to introduce specifi c genes to the mitochondria (Rinaldi et al 2010 ).…”
Section: The Mitochondrial Transformationmentioning
confidence: 99%
“…In line with the evolutionary conservation of disease genes in eukaryotes, it has been extensively shown that several disease-associated cellular pathways are also highly conserved from yeast to humans 113436, enabling the modeling of specific disease aspects in this model organism. Protein quality control systems 37, vesicular trafficking and secretion 38, autophagic pathways 39, the unfolded protein response 40, and mitochondrial biogenesis and metabolism 41 are among the conserved cellular mechanisms, allowing the study of fundamental mechanisms associated with neurodegenerative diseases, such as PD, in yeast cell models 11.…”
Section: The Power Of Yeast Geneticsmentioning
confidence: 99%